THE EXISTENCE OF THE BEAUTY TOWER IN MAINTAINING THE SAFETY AND SECURITY OF SHIPPING - Muh. Tahir; Danil Pasanda; Arif Maulana (UNES Law Review, 2023)
The Navigation Assistance Facility (SBNP) is an essential component that affects shipping safety and security, so a study was conducted to find out the role of the light tower guard in shipping and what obstacles were encountered in optimizing the part of the light guard. Normative research techniques to study the laws and regulations related to shipping implementation in Indonesia. The data came from statutes, regulations, expert theory, previous research, and books. The results showed that lighthouse keepers have two main objectives in shipping: assisting ship navigation in determining direction and location, warning ships when there is danger, and supporting shipping safety and security according to standards in SOLAS 1947 and ISM Code in the Shipping Law. The obstacles damaged buildings, electrical networks, installations, and light balloons that endangered shipping. The damage affects the performance of the light tower in determining the direction and location when the ship is sailing